2008
DOI: 10.2174/157340108783497418
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Actions of Polyunsaturated Fatty Acids in Cardiovascular Diseases: But, How and Why?

Abstract: Omega-3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and to a limited extent -6 fatty acids: arachidonic acid (AA), -linolenic acid (GLA) and dihomo-GLA (DGLA), prevent cardiovascular disease, thrombosis and atherosclerosis, reduce cardiac arrhythmias, lower plasma cholesterol and triglycerides, lower high blood pressure and improve endothelial function. These beneficial actions of the fatty acids could be attributed to their ability to augment endothelial nitric oxide generation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 323 publications
(435 reference statements)
0
12
0
Order By: Relevance
“…The latest overview found about the effect of omega-3 fatty acids in rheumatoid arthritis was published in 1998 (Ariza-Ariza, MestanzaPeralta, & Cardiel, 1998) although there is a more recent one (2006) not published in English (Stancík, Rovenský, & Stančíková, 2006). Several recent reviews on cardiovascular effects have also been recently published (Biscione, Pignalberi, Totteri, Messina, & Altamura, 2007;Tziomalos, Athyros, & Mikhailidis, 2007;vonSchacky & Harris, 2007;Das, 2008). vonSchacky and Harris (2007) proposed the omega-3 index (percentage of EPA + DHA of total fatty acids in red blood cells) as a risk factor for sudden cardiac death and concluded that this index should be higher than 8%.…”
Section: Omega-3 Fatty Acids and Human Healthmentioning
confidence: 99%
“…The latest overview found about the effect of omega-3 fatty acids in rheumatoid arthritis was published in 1998 (Ariza-Ariza, MestanzaPeralta, & Cardiel, 1998) although there is a more recent one (2006) not published in English (Stancík, Rovenský, & Stančíková, 2006). Several recent reviews on cardiovascular effects have also been recently published (Biscione, Pignalberi, Totteri, Messina, & Altamura, 2007;Tziomalos, Athyros, & Mikhailidis, 2007;vonSchacky & Harris, 2007;Das, 2008). vonSchacky and Harris (2007) proposed the omega-3 index (percentage of EPA + DHA of total fatty acids in red blood cells) as a risk factor for sudden cardiac death and concluded that this index should be higher than 8%.…”
Section: Omega-3 Fatty Acids and Human Healthmentioning
confidence: 99%
“…Commentary of adiponectin (because hypertensives have peripheral insulin resistance and are more prone to develop type 2 diabetes mellitus and metabolic syndrome 32 ); (g) depressed anti-oxidant capacity; (h) enhanced sympathetic tone (catecholamines have pro-inflammatory actions 33 ) and (i) low acetylcholine levels in the brain and leukocytes (because acetylcholine is an anti-inflammatory molecule, it enhances NO generation and its levels are enhanced by AA/EPA/DHA supplementation 34,35 ). Some of the suggested studies could be performed in human beings using peripheral leukocytes and macrophages because they contain the complete intracellular machinery for the generation, release and metabolism of dietary essential fatty acids, lipoxins, resolvins, protectins, maresins, nitrolipids, catecholamines, acetylcholine and serotonin, as well as the renin-angiotensin system and anti-oxidants.…”
Section: Linoleic Acid α-Linolenic Acidmentioning
confidence: 99%
“…Fatty acids in general and essential fatty acids in particular are very important to the body and are involved in the prevention of certain diseases. Epidemiological studies have demonstrated the importance of ω-3 fatty acids in human health and have shown the relationship between a ω-3 enriched diet and the prevention of certain diseases such as cardiovascular disease and myocardial infarction [26][27][28], intestinal disease [29], treatment and prevention of mental illness [30], prevention of several types of cancer [24,31] or bronchial asthma [32]. Subsequently, numerous epidemiological and clinical studies have focused on the effect of ω-3 PUFAs, in particular EPA and DHA, on human health and the mechanism by which this effect occurs.…”
Section: Resultsmentioning
confidence: 99%